TELAAH KEPERCAYAAN PUBLIK TERHADAP PANITIA PEMILIHAN KECAMATAN (PPK) DI PANYABUNGAN KOTA, KABUPATEN MANDAILING NATAL PADA PILPRES 2024 - Fadilah Nasution, Rizki; Nasution, Hasyimsyah (Penerbit Lafadz Jaya, 2025)
In the context of election administration, trust refers to public confidence that election institutions or committees (such as the Election Committee (PPK)) will carry out their duties honestly, fairly, transparently, and impartially. Public trust is a crucial element in realizing democratic, transparent, and integrity-based elections. The PPK, as the election organizer at the sub-district level, plays a strategic role in ensuring the election process runs according to honest and fair principles. This research uses a descriptive approach with qualitative methods, supported by quantitative data from a public questionnaire. This study aims to assess the level of public trust in the Sub-district Election Committee (PPK) for the 2024 Election in West Panyabungan District, Mandailing Natal Regency. This study aims to examine the level of public trust in the Sub-district Election Committee (PPK) Election in West Panyabungan city, Mandailing Natal Regency in the 2024 indonesian Presidential Election.